THE EXPERIENCES OF THE MOTHER OF AN ATYPICAL CHILD: NEGLECT VS OVERPROTECTION - Carolina Cortez, Ana; Figueiredo, Benedita; Cortez, Rafael; Rodrigues, Tatiane; Zolfan, Shirlei (Revista Gênero e Interdisciplinaridade, 2025)
This study analyzes the experience of motherhood for children with Autism Spectrum Disorder (ASD), with an emphasis on the difficulties faced by mothers and the consequences for their mental health. The research highlights the importance of understanding the particularities of the care provided to these children. In addition, the analysis shows that both parental neglect and overprotection can arise as responses to the complex demands of ASD, highlighting the need for support networks and appropriate interventions.